The magnetic early B-type stars – III. A main-sequence magnetic, rotational, and magnetospheric biography. Issue 1 (12th September 2019) - Shultz, M E; Wade, G A; Rivinius, Th; Alecian, E; Neiner, C; Petit, V; Owocki, S; ud-Doula, A; Kochukhov, O; Bohlender, D; Keszthelyi, Z; ,
ABSTRACT: Magnetic confinement of stellar winds leads to the formation of magnetospheres, which can be sculpted into centrifugal magnetospheres (CMs) by rotational support of the corotating plasma. The conditions required for the CMs of magnetic early B-type stars to yield detectable emission in H α – the principal diagnostic of these structures – are poorly constrained. A key reason is that no detailed study of the magnetic and rotational evolution of this population has yet been performed. Using newly determined rotational periods, modern magnetic measurements, and atmospheric parameters determined via spectroscopic modelling, we have derived fundamental parameters, dipolar oblique rotator models, and magnetospheric parameters for 56 early B-type stars. Comparison to magnetic A- and O-type stars shows that the range of surface magnetic field strength is essentially constant with stellar mass, but that the unsigned surface magnetic flux increases with mass. Both the surface magnetic dipole strength and the total magnetic flux decrease with stellar age, with the rate of flux decay apparently increasing with stellar mass. We find tentative evidence that multipolar magnetic fields may decay more rapidly than dipoles. Rotational periods increase with stellar age, as expected for a magnetic braking scenario. Without exception, all stars with H α emission originating in a CM are (1) rapid rotators, (2) strongly magnetic, and (3) young, with the latter property consistent with the observation that magnetic fields and rotation both decrease over time.